Establishment of a Somali Regional Technical Veterinary School and Reference Centre (STVS) Phase II. - African Union Inter-African Bureau for Animal Resources (My University, 2021)
• In 1990, agriculture contributed 65% of Gross Domestic Product (GDP) of Somalia including the livestock sector which accounted for between 40- 50%. FSAU (2002) estimates that the livestock sector now provides 55 `)/0 of the caloric intake of the population as well as 60 % of their income. In light of its economic importance, the Somali livestock export sector requires efficient and effective veterinary support services in order to compete with other livestock exporting countries. • Against this dynamic and competitive background, the available Somali veterinary support services are lacking and the general technical competence is dwindling. There have been no new graduates on any level of veterinary training since 1990. • Priority activities for Somali veterinary services are as follows: Control of epizootic diseases and certification of the health of livestock and livestock products for export, Protection of public health through control of zoonotic infections, Alleviation of husbandry related diseases and disorders affecting productivity of livestock. • Against this background Sheikh Technical Veterinary School (STVS) was designed with the overall objective to ensure that Somali people have access to efficient and effective veterinary services in order to safeguard public health, improve livestock production and animal welfare, and sustain livestock export. The project purpose is to establish a regional technical veterinary training and reference centre educating sufficient numbers of young professionals and responding to demands from the Somali livestock industry. • Phase 1 of STVS started in December 2001 and was due for completion in July 2003. Progress was slow due to delays in approval of the site allocation for the school in Sheikh, the need to run a pre-entry foundation course for the students and uncertainty about the scale of building works. Phase I was extended twice up to May 2004 followed by bridging phases until the present phase 2 was approved and a grant contract signed, starting in July 2005. • The overall objective for the STVS project has been defined as: Veterinary services in the Somali region safeguard public health, protect animal wel- - fare, improve livestock production and sustain livestock export. • The specific objective (purpose) of STVS has been defined as: A regional veterinary training system supplies competent technicians and provides professional advice to major stakeholders involved in the Somali livestock industry. • For Phase 2 of the project the following expected results were formulated: 1) STVS conducts a fully recognised veterinary diploma course on a regular basis; 2) STVS is recognised by the stakeholders of the Somali livestock industry as a technical reference centre; 3) Institutional framework of the school and administrative set-up is fully developed. • Phase 2 of the project started under the grant contract no SO/0038/ITCOF/ 05 on 1St July 2005. The duration of the contract is 30 months, ending 31st December 2007. The recipient organisation is Terra Nuova. The total contracted amount is € 2,210,506, of which € 2,100,000 is contributed by EC with Italian co-funding. • At the very start the project experienced a rapid turnover of managers, tutors in the Sheikh school, and a change of project co-ordinators in the Terra Nuova Regional Office in Nairobi. This situation has stabilised now and management and staff development are very promising. In the meanwhile the project has produced three extensive interim technical reports which had used the project's logframe as a guideline to evaluate achievements. • Several indicators used in the original logframe for Phase 2 are unrealistic. This applies to the project purpose as well as to the results level. • Assumptions and risks are formulated in a soft and non-committal fashion. Project ownership has not been defined, consequently long-term institutional and donor commitment is lacking. This is a severe drawback for the process of accreditation and for the general sustainability of the project. Again this will be discussed in more detail under Section E. • All activities listed for result 1 (STVS conducts a veterinary diploma course on a regular basis) were successfully implemented and achievement of result 1 was rated highly satisfactory. STVS is conducting coursework now in the third year and has consistently developed and improved all aspects of teaching, training and administrating academic work. There was some initial delay in the rehabilitation of the school buildings due to the fact that the second international NGO, originally in charge of this pulled out of the project. In the meanwhile the work has started and will be finished before the end of Phase 2. • Achievements under result 2 (STRVS is recognised as a technical reference centre) were rather mixed but none was highly satisfactory. This is basically to blame on overoptimistic planning from the very start of the project. The rather ambitious result was obviously expected to be achieved without a separate budget, without personnel assigned and without carefully planned infrastructure and facilities. If the reference centre is still considered a vital part of STVS this has to be amended for an anticipated next project phase. At least some of the needed physical facilities will become available once the final premises will be finished. • Result 3 is both the most important and the most difficult since it is strongly linked to all questions of the sustainability of STVS. Although substantial legal advice was provided through an expert employed by Terra Nuova no progress was made in finding a legal framework for STVS against the difficult political situation in Somalia. Long-term ownership and responsibility for STVS has not been established. Efforts in that direction undertaken by Terra Nuova need to be acknowledged but no other stakeholder made any productive contribution to a solution of the problem. Closely linked to and depending on the legal status are all other aspects of sustainability like accreditation, business plans, funding issues, and management structures. • The project management of STVS at the time of the MTE was solid and effective and able to respond to all matters arising from the day-to-day running of the classes in Sheikh as well as all other academic activities. The building activities are making good progress and will be finished before the end of Phase 2. Links with the local livestock sector and related projects have been formed and are yielding benefits to STVS. There is regular involvement of the steering committee and thorough internal monitoring and evaluation is carried out. There are a number of smaller changes in the finance plan but they are cost neutral with reference to the overall budget. Budget changes are mainly in relation to staff changes with a certain shift towards expatriate (regional) staff. • Like with all projects in tertiary education impact and effectiveness will become noticeable only after a longer time. The best indicator will always be the first graduate returning to the institution as a teacher. In the case of STVS I would estimate that a proper impact evaluation will become possible earliest after another five to six years of continued operation and external support. • STVS has almost achieved technical sustainability. The bulk of the investments will be implemented by the end of phase 2. The school's demonstration farm, the teaching clinic, and a service laboratory as part of the reference centre could be installed easily and cost-effectively early in a potential Phase 3. Once this has been done investment needs will go down to maintenance level. • Financial sustainability, business plans, and funding requirements will depend on establishing ownership and a legal framework for STVS. Terra Nuova and the STVS management and staff have prepared the way for a much needed and sustainable contribution to economic security in the Somali Ecosystem. In the process more than 4 million Euros were spent. It is high time for some of the institutional stakeholders to show political commitment.
Keywords: Veterinary Education Establishments